Pengaruh Ukuran Perusahaan, Umur Perusahaan, Current Ratio, Debt to Equity Ratio dan Fixed Asset to Total Asset Ratio terhadap Kinerja Keuangan pada Perusahaan Manufaktur di Bursa Efek Indonesia - Arisadi, Yunita Castelia; Djumahir, .; Djazuli, Atim (Jurnal Aplikasi Manajemen, 2013)
Investing in a listed company, investors need a solution to decide whether a company have a good performance or not. This research aimed to analyze the effect of firm size, firm age, current ratio, debt to equity ratio and fixed asset to total asset ratio to financial performance of manufacturing company in Indonesia Stock Exchange. This research used quantitative approach by implementing multiple regression analysis. This research population is all manufacturing companies listed in Indonesia Stock Exchange in the period of 2007-2011. There are 58 companies in 5 years period that had been choosen from a sensus method to become the sample. The result shows that firm size, current ratio, debt to equity ratio, and fixed asset to total asset ratio are affecting the financial performance of manufacturing company in Indonesia Stock Exchange. While firm age is not affecting the financial performance of manufacturing company in Indonesia Stock Exchange. The result of this research can become a consideration for company managers in making a decision to improve the financial performance of a company and make a lead to create an effective way of financial system. This research can be used for a reference to another researcher that also like to make an advanced study of factors that affecting financial performance of a company.